The Impact of Air Pollution on Human Health and Some Components of the Natural Resources - Dahlan, Endes N (Media Konservasi, 2011)
Carbon-monoxide, chloro-fluorocarbon, nitrogen-oxides, carbondioxide, sulfur-oxides, hidrocarbons, particulate matters and others are known as potential air pollutants. These compounds can be released by automobiles, electric power' generators, industries, household, agricultural burningsand forest fires. Air pollutants can be harmful to human beings directly or indirectly. They may cause melanoma (skin cancer), alopecia, angina pectoris, bronchitis, emphysema, asphyxia etc., and they can also disturb buildings, agricultural crops, forest vegetation, wildlife, water, soil, climate, and other natural resources.